Effects of dietary lipids on cell proliferation of murine oral mucosa - Actis, A. B. (2002)
Background: The lack of certain essential polyunsaturated fatty acids (PUFAs) induces perturbation in cell proliferation, apoptosis and dedifferentiation that could be linked to an increased protumorigenic trend. Contrarily, n-3 essential fatty acids (EFAs) arrest cell proliferation in several tumor models. According to the concept of field cancerization, multiple patches of abnormal epithelial proliferation may coexist in the vicinity of oropharyngeal neoplasms. The purpose of the present study is to determine whether certain dietary PUFAs differentially modulate the patterns of cell proliferation and apoptosis at non-tumoral sites of the oral mucosa in mice bearing DMBA induced salivary tumors. After weaning, BALB/c mice were assigned to four diets: Control (C), Corn Oil (CO), Fish (FO) and Olein (O). Two weeks later, DMBA was injected into the submandibular area. The animals were sacrificed between 94 and 184 days at 4–6 PM. Fixed samples of lip, tongue and palate were stained using H-E and a silver technique. A quantification of AgNORs in the basal (BS) and suprabasal stratum (SBS) of the covering squamous epithelia as well as of mitosis and apoptosis was performed. Results: Analysis of Variance showed greater proliferation in tongue than in palate or lip. According to the diet, a significant difference was found in the Fish Oil, in which palate exhibited fewer AgNOR particles than that of the control group, both for BS and SBS (p < 0.05 and 0.152, respectively), indicating a reduced cell proliferation. Conclusions: These results corroborate and reaffirm that the patterns of cell proliferation, apoptosis and differentiation of the oral stratified squamous epithelium may be differentially modulated by dietary lipids, and arrested by n-3 fatty acids, as shown in several other cell populations.